IPTEKS PERATURAN PEMERINTAH NO.71 TAHUN 2010 TENTANG AKUNTANSI PEMERINTAHAN BERBASIS AKRUAL PADA BADAN PENANGGULANGAN BENCANA DAERAH PROVINSI SULAWESI UTARA - Pinatik, Trianti K. A.; Tumanduk, Leonardo; Budiarso, Novi Swandari (Universitas Sam Ratulangi, 2018)
Organization of Prov. Regional Disaster Management Agency North Sulawesi Moves in the Field of Disaster Management Operations Centers which need to implement Government Regulation No. 71 of 2010 on accrual bases to provide information from financial records and facilitate more effective performance. In accounting there are two records of the first cash basis and accrual basis. Accrual Basis is the basis for facilitating performance measurement, in regulating clearer and more understandable. This study uses descriptive research methods that aim to explain the circumstances, events or everything related to programs that can be explained in words or numbers. The application of Government Regulation No. 71 of 2010 concerning accrual basis is certainly in accordance with what has been implemented by the Law that has been implemented by the government, Government Accounting Standards, Financial Accounting Standards. Accrual basis application needs financial statements, so that problems can be found or what things are not in accordance with the activities of either budgeting or calculation of budgeting.Keywords: Accrual Basis, Government Accounting, Government Accounting Standards, Financial Accounting Standards, Descriptive Methods.